Odpowiedź :
(x²)⁷× x³× x x¹⁴ × x³ x¹⁷
----------------= ------------= --------------= x¹⁷ - x⁷= x¹⁰
(x³)²×² x⁶ × x x⁷
2⁴×2⁵×2⁰×2⁻¹ 2⁹×1×½ 2⁹×½
----------------= ------------=--------- 2⁹×½:2⁷= 2⁹:2⁷×½=2²×½=2²×½
2³×2⁴ 2⁷ 2⁷
=4×½=2
----------------= ------------= --------------= x¹⁷ - x⁷= x¹⁰
(x³)²×² x⁶ × x x⁷
2⁴×2⁵×2⁰×2⁻¹ 2⁹×1×½ 2⁹×½
----------------= ------------=--------- 2⁹×½:2⁷= 2⁹:2⁷×½=2²×½=2²×½
2³×2⁴ 2⁷ 2⁷
=4×½=2
(x²)⁷× x³×x/ (x²)³× x²=x¹⁴× x³× x/ x⁶× x²=x¹⁸/x⁸=x¹⁰
2⁴× 2⁵×2⁰×2⁻¹/2³×2⁴=2⁸/2⁷=2¹=2
2⁴× 2⁵×2⁰×2⁻¹/2³×2⁴=2⁸/2⁷=2¹=2
(x²)⁷*x³*x
(x³)²*x²
najpierw policzę to nad kreską
(x²)⁷*x³*x=x¹⁴*x³*x=x¹⁸
teraz dolna
(x³)²*x²=x⁶*x²=x⁸
a teraz razem
x¹⁸÷x⁸=x¹⁰
2⁴*2⁵*2⁰*2⁻¹
2³*2⁴
i tak jak poprzednio
2⁴*2⁵*2⁰*2⁻¹=2⁸
i dolna
2³*2⁴=2⁷
2⁸÷2⁷=2¹=2
(x³)²*x²
najpierw policzę to nad kreską
(x²)⁷*x³*x=x¹⁴*x³*x=x¹⁸
teraz dolna
(x³)²*x²=x⁶*x²=x⁸
a teraz razem
x¹⁸÷x⁸=x¹⁰
2⁴*2⁵*2⁰*2⁻¹
2³*2⁴
i tak jak poprzednio
2⁴*2⁵*2⁰*2⁻¹=2⁸
i dolna
2³*2⁴=2⁷
2⁸÷2⁷=2¹=2